WIRETAPPING ON SUBMARINE COMMUNICATIONS CABLE: QUESTIONING ITS LEGALITY AMIDST LONG STANDING PRACTICE - Hafidz L. Botua; Chloryne Trie Isana Dewi; R. Achmad Gusman Catur Siswandi (International Law Department, Faculty of Law Universitas Padjadjaran, 2022)
Up to 95% of the communication infrastructures are currently served by the submarine communications cable networks, which in their utilisation connect a wide variety of communications data. The increasingly advanced infrastructure is in fact unable to go hand in hand with legal transformation. At the present time, international law provides only partial protection in form of prevention against damage to the cable networks. Consequently, in the event that data transmissions across the cable networks are illegally exploited by foreign parties through